Dueling : The Cult of Honor in Fin-de-Siècle Germany - McAleer, Kevin, 1961- (Book collections on Project MUSE., 1994)
The question of what it takes ""to be a man"" comes under scrutiny in this sharp, often playful, cultural critique of the German duel--the deadliest type of one-on-one combat in fin-de-siecle Europe. At a time when dueling was generally restricted to swords or had been abolished altogether in other nations, the custom of fighting to the death with pistols flourished among Germany's upper-class males, who took perverse comfort in defying their country's weakly enforced laws. From initial provocation to final death agony, Kevin McAleer describes with ironic humor the complex protocol of the Ger.